Analisis Risiko Operasional Berdasarkan Pendekatan Enterprise Risk Management (ERM) Pada Roti Kukus Manju Cabang Tuasan - Pardede, Ronaldo; Gey Des Four Munte; Deyan Andini Zam Zam Nasution; Rossy Pratiwi Sihombing; Putri Kemala Dewi Lubis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In running a business there are definitely risks. Risks that arise from the internal and external environment of the business can result in the business experiencing losses. This research method uses a qualitative descriptive research method with data collection techniques originating from observations and interviews with the owner of the Manju Steamed Bread business, Tuasan Branch. This research will use Enterprise Risk Management (ERM), where ERM implementation is usually implemented by identifying risks, assessing and controlling risks. Businesses that use Enterprise Risk Management (ERM) can get risks ranging from low (low), medium (medium), high (high). This research aims to identify risks that may occur in the Manju Steamed Bread business, Tuasan Branch, then create a risk matrix to determine the worst risks that must be prioritized in control. The research results show that there are operational risks, namely employees not following steaming machine operating procedures, lack of maintenance of the machine and bread steaming equipment by employees and delays in the arrival of raw materials. This risk will affect the quality of taste, service, and can result in losses due to shop closures due to delays in the arrival of raw materials, so risk management is needed which aims to reduce operational risks that may occur.